THE INFLUENCE OF CONFORMITY CONSUMPTION BEHAVIOR AND PRODUCT ATTRIBUTES ON THE DECISION TO PURCHASE SKINCARE PRODUCTS : (Study in State University Students in the City of Medan) - Simanjuntak, Eva Yohana; Marpaung, Nicholas (Transpublika Publisher, 2024)
This study aims (1) to determine the effect of Conformity Consumption Behavior on purchasing decisions for skin care products, (2) to ascertain the impact of Product Attributes on the purchasing decisions of skin care products, and (3) to examine the combined influence of Conformity Consumption Behavior and Product Attributes on purchasing decisions for skin care products. The research employs a quantitative method. The results of this study yield a multiple linear regression equation: Y = 6.453 + 0.172 X1 + 0.647 X2. Partially, Conformity Consumption Behavior demonstrates a positive and significant effect, as evidenced by a t-value value of 2.571, exceeding the t-table value of 1.1985. Similarly, Product Attributes exhibit a positive and significant effect, with a t-value of 8.830 surpassing the t-table value of 1.985. Simultaneously, the combined impact of Conformity Consumption Behavior and Product Attributes on the decision to purchase skin care products is demonstrated by an F-value of 77.803, surpassing the F-table value of 3.09. Notably, the variable with the most dominant influence in this study is Product Attributes, with a value of 8.830.